Antimicrobial Management of Respiratory Infections in Severe Acute Respiratory Syndrome Coronavirus 2 Patients: Clinical and Antimicrobial Stewardship Programs Conundrums. (26th October 2020) - Goldstein, Ellie J C; Tillotson, Glenn; Redell, Mark
Abstract: The role of empirical and even directed antimicrobial management of patients hospitalized with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is problematic; antibiotics are used frequently among these patients to treat confirmed or suspected coinfection or just the symptoms. In the rapidly changing clinical landscape of SARS-CoV-2, there is minimal guidance for selecting appropriate treatment versus non-antimicrobial treatment, and clinicians are pressed to make daily decisions under the stress of absence of data while watching patients deteriorate. We review current data and patterns of antimicrobial use and the potential approach for antimicrobial stewardship in the context of SARS-CoV-2.